From Profit to Planet: A Systematic Review of Cost Accounting in Fast Fashion - Rakhmawati, Henny (International Ecsis Association, 2025)
The fast fashion industry, characterized by rapid production cycles and low-cost clothing, has raised significant concerns regarding environmental degradation and labor exploitation. This study aims to examine how cost accounting practices can be integrated with sustainability frameworks to address the hidden costs of fast fashion. Employing a systematic literature review (SLR) guided by the PRISMA protocol, over 100 peer-reviewed articles were analyzed from databases including Scopus, Web of Science, and ProQuest. The selected literature was assessed using the CASP checklist and synthesized through thematic narrative analysis focused on cost structure, sustainability accounting, and operational efficiency. The findings reveal that traditional cost accounting tools such as standard costing and activity-based costing (ABC) are widely applied in fast fashion firms but remain inadequate in capturing environmental and social costs. Integrated approaches, including Environmental Management Accounting (EMA), the Triple Bottom Line (TBL), and lifecycle costing, offer more comprehensive frameworks for aligning profitability with sustainability. These insights highlight the need for fashion companies to shift from short-term cost minimization to long-term value creation strategies. The study implies that revising cost structures is essential to support ethical and sustainable business models. Its main contribution lies in proposing a conceptual framework for sustainable cost accounting tailored to the fast fashion industry.